Analysis of Judges' Considerations in Determining Child Support after Divorce (Study of Judge's Decision Number 0233/Pdt.G/2017/MS-MBO) - Muhammad Adipa Ghaza Al Azmi; M. Junaidi; Tomás Mateo Ramon (Proceeding International Conference Restructuring and Transforming Law, 2023)
A child's livelihood is everything a child needs to grow and develop, for example food, clothing and shelter. The responsibility for child support lies with the parents. However, in the case of divorce, the father is still responsible for the child's life even though the child is being raised by the mother. The child's income level does not determine the minimum or maximum gross income that must be adjusted to the father's economic strength. If the father cannot really provide for the child's needs, the responsibility for the child's expenses lies with the mother. Judge's decision no. 0233/Pdt.G/2017/MS_MBO shows that the panel of judges reduced the nominal amount of child support requested by the defendant from the plaintiff. The child's expenses were initially claimed to be IDR 1,600,000, - set by the jury at only IDR 600,000, - with an additional 20% per year, the child's income will be reduced compared to the IDR originally requested. Therefore, this article will be serious about the basis of the judge's intention to reduce the amount of child support and how the child's income is determined according to Islamic law. The research methods used are field research and library research. The results of the study explain that the main basis for the judge's consideration was to reduce the child's income by the amount required due to the father's inability to pay for it. Second, the determination of child support in the decision is in accordance with Islamic law because the rules of Islamic law explain that the implementation of child support by the father must be in accordance with the father's financial capabilities.